Translation and validation of Malay language version of the patient-physician relationship survey (PPRS) (patient version) and determinants of an effective patient-physician relationship in the management of irritable bowel syndrome - Ling, Ooi Seok (2021)
Background Irritable bowel syndrome is prevalent and its therapy involves multi-pronged approaches. An effective patient-physician relationship (PPR) often affects the treatment outcome but its determinants are not fully known. PPR can be assessed using a newly developed PPR questionnaire, but this tool has not been translated and validated in Malay language. Method The original English PPR survey (PPRS) (patient version) was first translated into Malay language, using a standard forward and backward translation approach. Subsequently, to validate the translated PPRS questionnaire, it was administered to patients with irritable bowel syndrome (IBS) (based on the Rome IV criteria), recruited sequentially using a cross-sectional design. Exploratory factor analysis (EFA) and reliability analysis were performed to determine the psychometric properties of PPRS. A validated Malay-version of SKIP-11 questionnaire (a survey to assess patient satisfaction and probably the closest to PPRS) was administered concomitantly to determine the comparative validity of PPRS. Comparative mean and regression analyses were conducted to explore the determinants of effective PPRS in the management of IBS. Results The EFA yielded three factors. The Kaiser-Meye-Olkin was 0.798. Bartlett’s test of sphericity was significant (P <0.001). The final Malay-translated PPRS consisted of three domains with 28 items. The domains included interpersonal features, clinical care expectations and aspects of communication. The internal consistency was satisfactory (Cronbach’s alpha 0.932). For the determinants of effective PPR, a total of 80 patients with irritable bowel syndrome with the mean age 52, 70% Malay and 52.5% female had responded. Factor analysis showed marital status(single) (median36, interquartile range 14; P-value 0.038) and household income (higher income) (mean score 37.67, SD 7.98; P-value 0.02) were the significant determinants of effective PPR. There was a fair significant correlation between PPRS and SKIP-11(r=0.3, P =0.007). Conclusion The study suggested that the Malay-translated PPRS (patient version) is a valid and reliable tool to be used to assess PPR. Marital status of single and high household income are the determinants of effective PPR in IBS.